2020
DOI: 10.1186/s12915-020-0743-4
|View full text |Cite
|
Sign up to set email alerts
|

The quail genome: insights into social behaviour, seasonal biology and infectious disease response

Abstract: Background: The Japanese quail (Coturnix japonica) is a popular domestic poultry species and an increasingly significant model species in avian developmental, behavioural and disease research. Results: We have produced a high-quality quail genome sequence, spanning 0.93 Gb assigned to 33 chromosomes. In terms of contiguity, assembly statistics, gene content and chromosomal organisation, the quail genome shows high similarity to the chicken genome. We demonstrate the utility of this genome through three diverse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 123 publications
(172 reference statements)
0
39
1
6
Order By: Relevance
“…2018) and Japanese quail (Morris et al . 2020) were developed. As our experiment with several full‐ and half‐sib families and approximately 1000 animals across three generations can be seen as a powerful linkage mapping design, we developed a further linkage map.…”
Section: Discussionmentioning
confidence: 99%
“…2018) and Japanese quail (Morris et al . 2020) were developed. As our experiment with several full‐ and half‐sib families and approximately 1000 animals across three generations can be seen as a powerful linkage mapping design, we developed a further linkage map.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared these sequences with Japanese quail protein sequences that were available in databases. The most recently published quail genome is by Morris et al (2020). They stated that the genome sequence of Coturnix japonica is close to completion.…”
Section: Calpeptin Does Not Inhibit Myofibrillogenesismentioning
confidence: 99%
“…In addition, the Japanese quail shows close phylogenetic relatedness to chickens with similar length of genome, chromosome number, and morphology of chromosomes. Therefore, a high rate of contiguity, assembly statistics, gene content, chromosomal organization, and synteny conservation exists between the two species [ 42 , 80 ]. Knaga et al [ 31 ] reported QTL for the egg number and egg production rate at positions 36 to 42 cM on chromosome 1 using 30 microsatellite markers.…”
Section: Discussionmentioning
confidence: 99%